2019
DOI: 10.1016/j.kint.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Novel ELISA for thrombospondin type 1 domain-containing 7A autoantibodies in membranous nephropathy

Abstract: T he primary form of membranous nephropathy (MN) is an autoimmune kidney disease in which circulating autoantibodies target podocyte autoantigens, leading to deposition of immune complexes in the glomerular capillary wall, podocyte injury, and proteinuria. 1-3 Overall, MN affects more men than women (sex ratio 2:1), with a peak incidence at 50 to 55 years. 4,5 Clinical outcome varies from spontaneous remission to persistent proteinuria and end-stage renal disease in about 30% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 80 publications
0
71
0
3
Order By: Relevance
“…Although anti-PLA 2 R Ab was considered a reliable biomarker for primary MGN [5], its appearance in secondary MGN was not surprising since the biomarker was reported to be associated with hepatitis B virus infection [14,15]. A biomarker, anti-THSD7A Ab can be used to make a diagnosis of primary MGN variants not detected by anti-PLA 2 R Ab [16]. In this study, serum anti-THSD7A Ab was positive in four biopsy-proven primary MGN subjects and two secondary MGN subjects (one of which was associated with malignancy and the other was due to lupus nephritis type V).…”
Section: Role Of Biomarkers (Pla 2 R and Thsd7a) In The Diagnosis Of Mgnmentioning
confidence: 99%
“…Although anti-PLA 2 R Ab was considered a reliable biomarker for primary MGN [5], its appearance in secondary MGN was not surprising since the biomarker was reported to be associated with hepatitis B virus infection [14,15]. A biomarker, anti-THSD7A Ab can be used to make a diagnosis of primary MGN variants not detected by anti-PLA 2 R Ab [16]. In this study, serum anti-THSD7A Ab was positive in four biopsy-proven primary MGN subjects and two secondary MGN subjects (one of which was associated with malignancy and the other was due to lupus nephritis type V).…”
Section: Role Of Biomarkers (Pla 2 R and Thsd7a) In The Diagnosis Of Mgnmentioning
confidence: 99%
“…23 Thus, with regard to PLA2R, a retrospective study showed 89.6% prevalence of PLA2Rassociated MN at the Tenon Hospital, 24 while there was a prevalence of only 48.1% among 592 biopsies of nonlupus MN at the Mayo Clinic (S. Sethi, 2019, unpublished data). Similarly, a recent study on THSD7A-associated MN reported a prevalence of 2.8% among the 1012 patients from 6 European cohorts, 25 while only 1 of 181 patients enrolled in Membranous Nephropathy Trial of Rituximab (MENTOR) study, 26 and 2 of 422 (<0.5%) patients screened at Mayo Clinic locations-Rochester, MN; Jacksonville, FL; and Phoenix, AZ-were found to be THSD7A positive (S. Sethi, 2019, unpublished data).…”
Section: Discussionmentioning
confidence: 80%
“…It is defined by the presence of subepithelial immune complex deposits with alteration of the glomerular membrane and podocyte injury [2]. Most MN cases are associated with autoantibodies directed against podocyte antigens such as the M-type phospholipase A2 receptor (PLA2R1) [3] and thrombospondin type 1 domain-containing 7A (THSD7A) [4,5] in 70% and 3% of adult patients, respectively. Disease evolution is highly variable from spontaneous remission to persistent proteinuria or end-stage renal disease [6].…”
Section: Introductionmentioning
confidence: 99%